Proceedings of the 16th Meeting on the Mathematics of Language 2019
DOI: 10.18653/v1/w19-5707
|View full text |Cite
|
Sign up to set email alerts
|

Efficient learning of Output Tier-based Strictly 2-Local functions

Abstract: This paper characterizes the Output Tier-based Strictly k-Local (OTSL k) class of string-tostring functions, which are relevant for modeling long-distance phonological processes as input-output maps. After showing that any OTSL k function can be learned when k and the tier are given, we present a new algorithm that induces the tier itself when k = 2 and provably learns any total OTSL 2 function in polynomial time and data-the first such learner for any class of tier-based functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Finally, future work will consider the learnability of MTSL functions. Burness and McMullin (2019) showed that any OTSL function is efficiently learnable from positive data if the tier is known in advance. This result can likely be carried over to MTSL functions once they receive a suitable automata characterization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, future work will consider the learnability of MTSL functions. Burness and McMullin (2019) showed that any OTSL function is efficiently learnable from positive data if the tier is known in advance. This result can likely be carried over to MTSL functions once they receive a suitable automata characterization.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in Burness and McMullin (2019), the TSL functions are quite versatile, being able to model long-distance harmony and long-distance dissimilation, both with and without blocking effects. This is, however, only the case when we model each phonological process of a language in isolation.…”
Section: Limitations Of Tsl Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has suggested that learnability of non-adjacent dependencies in phonology may require parsing vowels and consonants on different tiers (Burness & McMullin, 2019;Chandlee, 2014;Heinz, 2010;McMullin, 2016;Newport & Aslin, 2004), and that learners show biases against root and pattern morphology with roots that contain a mix of consonants and vowels (Fullwood, 2018).…”
mentioning
confidence: 99%